RENAL PELVIC TRANSITIONAL CELL CARCINOMA – SQUAMOID VARIENT WITH VENA CAVAL THROMBUS MIMICKING RENAL CELL CARCINOMA. - Hanan Noor; Muhammad Sohail; Muhammad Tahir Bashir Malik; Muhammad Akram Malik (Journal of University Medical & Dental College, 2018)
ABSTRACT:A 56 year old female presented with complaint of episodic gross hematuria & bilateral lumber pain. CT scan abdomen and pelvis revealed Rt. Renal mass complicated by Rt renal vein thrombus & Left Renal and ureteric stones with relatively delayed contrast enhancement. A Right Extended subcostal incision was used to perform Rt radical Nephrectomy. Per operatively Rt. Kidney was adherent to inferior vena cava medially. Tumor thrombus retrieved from inferior vena cava (T3b thNoMo) via venotomy after triangular controlled achieved. Patient was discharged on 8 post operative day. The pathological diagnosis was turned out to be high grade, Transitional cell carcinoma of renal pelvis with squamoid diﬀerenciation. Nephroureterectomy with bladder cuﬀ excision was planned. The patient came on follow up and refused any adjuvant therapy. Tumor recurrence was detected, referred for adjuvant therapy and the patient died of cancer 3 months after the surgery.